2020
DOI: 10.1038/s41598-020-77483-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyrhythmic foraging and competitive coexistence

Abstract: The current ecological understanding still does not fully explain how biodiversity is maintained. One strategy to address this issue is to contrast theoretical prediction with real competitive communities where diverse species share limited resources. I present, in this study, a new competitive coexistence theory-diversity of biological rhythms. I show that diversity in activity cycles plays a key role in coexistence of competing species, using a two predator-one prey system with diel, monthly, and annual cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…The size of the competitive coefficients, 𝛼, will also be altered by the timescales in a similar manner. In what follows, we find results that occur across broad swaths of r and 𝛼 values suggesting that our results likely hold for a broad range of natural periodicities (e.g., days to multidecadal), consistent with a recent analysis by Mougi (2020) which argued that scales of months to years ought to significantly aid species coexistence.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The size of the competitive coefficients, 𝛼, will also be altered by the timescales in a similar manner. In what follows, we find results that occur across broad swaths of r and 𝛼 values suggesting that our results likely hold for a broad range of natural periodicities (e.g., days to multidecadal), consistent with a recent analysis by Mougi (2020) which argued that scales of months to years ought to significantly aid species coexistence.…”
Section: Methodssupporting
confidence: 90%
“…These periodicities therefore impact species’ growth rates, but also offer the potential for differential responses of competing species to seasonally-driven environmental variation (Chesson and Huntly 1997; Forrest and Miller-Rushing 2010; Shuter et al 2012; Gao et al 2016; Chesson 2018; Huang et al 2019). It is well known that competing species can display temporal trade-offs in stochastic environments that can promote coexistence (Litchman and Klausmeier 2001; Angert et al 2009; Klausmeier 2010; Shuter et al 2012; Mougi 2020). For instance, Litchman and Klausmeier (2001) discovered that slow fluctuations in light promote stable coexistence between competing species of phytoplankton who exhibit temporal trade-offs in resource availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a more whitened noise) while aquatic and marine systems are skewed towards the lower frequencies characterizing brown and reddened noise [6,8]. As a first step towards bridging the gap between coupled environmental periodicities and ecosystem functioning, Mougi [5] used a spectrum of periodic environmental forcing to theoretically argue that species can coexist through trade-offs organized around the frequencies of nature's many rhythms, and Simon [9] showed that environmental frequencies may have complex interactions with cascading trophic dynamics. Further, researchers are beginning to show that some forms of periodic variation, like seasonality, may alter food web structure in a manner that maintains biodiversity by facilitating coexistence or stabilizing eco-evolutionary dynamics [10][11][12] and consumer-resource (C-R) interactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Given this, it is entirely possible that these fundamental periodicities could play a significant role in regulating the structure and function of ecosystems worldwide. Despite the recognition that such underlying periodicities abound and organisms have adapted to them, surprisingly little work has been done to incorporate these rhythms into our understanding of ecology [ 5 ]. This is more surprising considering climate change and, more broadly, global change are currently altering the nature of these underlying frequencies at a variety of scales [ 2 ].…”
Section: Introductionmentioning
confidence: 99%